Psychological and pedagogical assistance/support in an educational organization in Moscow: target groups of students - Egorova, L.V.; Matyushkova, N.Yu (Bulletin of Practical Psychology of Education, 2025)
Context and relevance. In line with priority urban objectives related to supporting students, the primary goal of psychological and pedagogical support services in Moscow schools is to create comfortable and safe conditions within the educational environment that promote successful development, socialization, and self-realization of each child in socially positive activities. The work of a school psychologist depends on the child's characteristics, specifics of their age and individual development, and family living conditions. According to the Standard of Activities of Psychological and Pedagogical Services in Moscow Education System, several categories or target groups of students are identified to enhance the effectiveness of provided support. Objective. To describe the key characteristics of target student groups as per the Standard of Activities of Psychological and Pedagogical Services in Moscow Education System, to examine the implementation of main directions of support, and to outline priority tasks addressed by educational psychologists within their competencies. Hypothesis. Psychological and pedagogical support for different target groups of students varies in objectives and content. Methods and materials. The methodological framework of the study is based on regulatory documents, theoretical concepts of Russian psychologists, and practical tools developed for Moscow education system. Additionally, a survey was conducted among educational psychologists in Moscow educational institutions with 290 specialists participating. Results. Psychological and pedagogical support for different target groups of students is tailored to their specific educational needs and individual characteristics, enabling conditions for successful socialization. Conclusions. Educational psychologists in Moscow educational institutions primarily provide psychological and pedagogical support to the target group of students with special educational needs, particularly those with disabilities who have a conclusion of the Moscow Central Psychological-Medical-Pedagogical Commission (CPMPС). Other target groups receive less coverage in terms of psychological and pedagogical support. Контекст и актуальность. В соответствии с приоритетными городскими задачами в части помощи и поддержки обучающихся основной целью в деятельности служб психолого-педагогического сопровождения московских школ является создание комфортных и безопасных условий образовательной среды, способствующих успешному развитию, социализации и самореализации в социально позитивных видах деятельности каждого ребенка. Содержание работы школьного психолога зависит от особенностей ребенка, специфики его возрастного и индивидуального развития, условий жизни в семье. Согласно Стандарту деятельности психолого-педагогических служб в системе образования г. Москвы, с целью повышения эффективности оказываемой помощи выделяют несколько категорий, или целевых групп, обучающихся. Цель. Описать ключевые особенности целевых групп обучающихся в соответствии со Стандартом деятельности психолого-педагогических служб в системе образования города Москвы, рассмотреть вопросы реализации основных направлений помощи и поддержки обучающихся, приоритетные задачи, решаемые педагогами-психологами в рамках своих компетенций. Гипотеза. Психолого-педагогическое сопровождение обучающихся различных целевых групп отличается по целям и содержанию. Методы и материалы. Методологическая база исследования основана на нормативных документах, теоретических концепциях отечественных психологов и практических инструментах, разработанных для системы образования г. Москвы. Также был проведен опрос среди педагогов-психологов образовательных организаций города Москвы, приняли участие 290 специалистов. Результаты. Психолого-педагогическое сопровождение обучающихся разных целевых групп имеет свою специфику, обусловленную особыми образовательными потребностями и индивидуальными особенностями детей, учитывая которые становится возможным создать условия для успешной социализации обучающихся. Выводы. Педагоги-психологи образовательных организаций города Москвы преимущественно оказывают психолого-педагогическую помощь/поддержку целевой группе обучающихся с особыми образовательными потребностями, в первую очередь, обучающимся с ОВЗ, имеющим заключение ЦПМПК г. Москвы. Обучающиеся других целевых групп в меньшей мере охвачены психолого-педагогический помощью.